2017
DOI: 10.1515/jee-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of output voltage distortion of inverter for frequency lower than the nominal

Abstract: The paper discussed the studies related to the output voltage distortion of frequency inverter depending on its frequency. The changes in the effective value of voltage, THD, harmonics and interharmonics were presented for three different frequencies, lower than 50Hz. Additionally, it was shown how these values change depending on measurement time, presenting waveforms cycle by cycle in graphs, averaged in 10 periods and averaged in 150 periods of the analyzed signal. The studies were conducted in the laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In order to gain the accurate assessment of the electrical waveform distortion, the distortion components have to be representative and integral to reality. The authors of numerous works [6], [8], [23], [24], [25], [26] indicate that restriction of the spectrum suggested in the norm [10] to 50 components may be the reason for the discrepancies. In work [23] presents the practical example of the supply voltage on a ship.…”
Section: E Crest Factormentioning
confidence: 99%
See 2 more Smart Citations
“…In order to gain the accurate assessment of the electrical waveform distortion, the distortion components have to be representative and integral to reality. The authors of numerous works [6], [8], [23], [24], [25], [26] indicate that restriction of the spectrum suggested in the norm [10] to 50 components may be the reason for the discrepancies. In work [23] presents the practical example of the supply voltage on a ship.…”
Section: E Crest Factormentioning
confidence: 99%
“…It was probably caused, among others, by a reduced range of analyzed spectrum, according to the norm [10]. Further studies [6], [26] indicated that narrowing the spectrum of harmonics may affect other parameters that describe electrical waveforms such as effective value (RMS), waveform distortion factor (THD), and crest factor (CF).…”
Section: E Crest Factormentioning
confidence: 99%
See 1 more Smart Citation